A novel two-step rating-based 'double-faced applicability' test. Part 2: Introducing a novel measure of affect magnitude (d′A) for profiling consumers' product usage experience based on Signal Detection Theory. (July 2017) - Kim, In-Ah; Hopkinson, Andrew; van Hout, Danielle; Lee, Hye-Seong
Highlights: A novel nonparametric measure of affect named as d-prime affect magnitude ( d ′ A ) was developed. d ′ A was computed using responses obtained from 'double-faced applicability' test. d ′ A reflected positive, negative or neutral group mean valence of each attribute. d ′ A values can be used to construct a profile of consumers' affective usage experience for each product. As d ′ A is computed per sample, multiple comparisons across samples could be visualized. Abstract: To measure consumers' product usage experience throughout the various product usage stages, a novel two-step rating-based 'double-faced applicability' test has recently been proposed by Kim et al. (2017). In this method, a 'two-step' rating (forced-choice Yes/No questions followed by 3-point sureness ratings) and 'double-faced' descriptors (a pair of semantic-differential descriptors) are used for each attribute to improve the product discriminability by reducing consumers' response bias and variations. In this paper, we introduce a novel measure that can be computed from the data from the 'double-faced applicability' test to provide a new way to generate affective product usage experience profiles. The novel measure was a nonparametric estimate of affect magnitude, named as d-prime affect magnitude ( d ′ A ), computed by considering the response ratio of positivity to negativity as the ratio of signal to noise in the context of Signal Detection Theory (SDT). The advantage of using this new measure d ′ A was that it meaningfully reflected the consumers' affective product usage experience for each product independently (and how this affect valence changed through a usage process), yet it can still be used to compare between products. The practical application of using d ′ A was demonstrated in comparison to the more conventional SDT measure d ′.